Eocene adakitic quartz monzonites and granite porphyries from the northern Qiangtang Block, central Tibet: Partial melting of sediment-rich mélange? - Xu, Chuan-Bing; Zeng, Ji-Peng; Wang, Qiang; Zhang, Xiu-Zheng; Ou, Quan; Wang, Jun; Hao, Lu-Lu; Chen, Yiwei (Frontiers in Earth Science, 2022)
The time and mechanism of crustal thickening and initial surface uplift of the Tibetan Plateau remain highly controversial. Here we report on zircon U-Pb age, element, and Sr-Nd-O isotope data for Eocene (41–37 Ma) quartz-monzonites and granite porphyries in the Qoima Co area of northern Qiangtang Block, central Tibet. The granite porphyries are characterized by high silica (72 wt%), adakitic trace elements, enriched Sr-Nd isotope ((87Sr/86Sr)i = 0.7074, εNd(t) = –4.5) signatures with zircon δ18O values of +6.28 ± 0.85‰. The quartz-monzonites exhibit high K2O contents (5.1–6.8 wt%) and K2O/Na2O ratios (1.3–2.3). They also display adakitic geochemical characteristics, such as low Y (12–25 ppm) and Yb (1.1–1.8 ppm) contents, high Sr/Y (98–187) and La/Yb (59–134), positive Sr and negligible Eu anomalies and Nb-Ta depletion. The quartz-monzonites have slightly variable initial 87Sr/86Sr ratios ranging from 0.7069 to 0.7078, εNd(t) values from –5.1 to –2.9, and δ18O values ranging from +6.27 ± 0.64‰ to +7.91 ± 0.32‰. We suggest that the granite porphyries were most probably derived by partial melting of thickened, sediment-bearing lower crust, and the quartz-monzonites were most probably generated by partial melting of sediment-rich mélange. Combining tectonic and geophysical data, we conclude that continental subduction and mélange underplating were possibly responsible for crustal shortening and tectonic thickening.